2015
DOI: 10.5530/jyp.2015.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Anti microbial Potential of Non-antibiotics on Resistant Bacteria – A Review

Abstract: The non-chemotherapeutic compounds, synthetic compounds and naturally isolated compounds possess good antimicrobial activity against microbial infections is a well-known fact. In this state the term non-antibiotics is taken to include a variety of pharmacologically active compounds which are useful in the management of pathological conditions of anon-infectious diseases that modify cell permeability and have been shown to exhibit broad spectrum antimicrobial activity. Of the nonantibiotic medicinal compounds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…4 It can lead to increased morbidity, mortality, length of hospital stay, and healthcare expenditures. 5,6 Inappropriate use of broad spectrum antimicrobials lead to decreases sensitivity of antimicrobials against microorganisms. Increasing multidrug resistance with limited availability of newer agents there is urgent need for vigilant surveillance, stringent infection control practices, as well as rational anti-biotic prescription.…”
Section: Introductionmentioning
confidence: 99%
“…4 It can lead to increased morbidity, mortality, length of hospital stay, and healthcare expenditures. 5,6 Inappropriate use of broad spectrum antimicrobials lead to decreases sensitivity of antimicrobials against microorganisms. Increasing multidrug resistance with limited availability of newer agents there is urgent need for vigilant surveillance, stringent infection control practices, as well as rational anti-biotic prescription.…”
Section: Introductionmentioning
confidence: 99%
“…When these drugs were used in combination there was an enhancement of the antibacterial capability against Gram (+)ve and Gram (-)ve micro organism. On the Pharmacol 2015;10: 875-883basis of MIC and disc diffusion method the antibacterial activity of mebeverine and troxipide and their following synergistic effect with an antibiotic ampicillin indicated that they act like non-antibiotics diclofenac sodium oxyfedrine omeprazole, ranitidine (Alkuraishy, 2011) dicyclomine (Karak et al, 2003), azelastin (El-Nakeeb et al, 2012;Akilandeswari et al, 2015). However, bacterial growth inhibition for both troxipide and mebeverine was achieved after 36 hours compared with the conventional antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Substituted phenothiazines have been used for the preparation of the polymers [13], the solar cells [14,15], biological stains [16], as well as medicaments [12]. They possess antimicrobial [6,[21][22][23][24], anthelmintic [7], antiemetic [8], antihistaminic [8] anticancer properties [2], and they are used in clinical practice more than 50 years as antipsychotics [12,17].…”
Section: Use and Applicationmentioning
confidence: 99%
“…The killing of intracellular bacteria promoted by phenothiazine can inhibit many transport processes of potassium and calcium pump activation. The increased permeability ensures phenothiazine molecules to reach the DNA, intercalate between the bases, inhibit the entire DNA and hence inhibit transcription and translation processes [21]. The ability of chlorpromazine to cure tuberculosis resulted in a series of in vitro studies that showed that chlorpromazine was more effective antimycobacterial compound than other N-alkylphenothiazines [21][22][23][24].…”
Section: Use and Applicationmentioning
confidence: 99%
See 1 more Smart Citation